2016
DOI: 10.3390/ma9080629
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Thermoelectric Performance of Cu2SnSe3-Based Composites Incorporated with Nano-Fullerene

Abstract: In this study, nano-sized fullerene C60 powder was sufficiently mixed with Cu2SnSe3 powder by ball milling method, and the C60/Cu2SnSe3 composites were prepared by spark plasma sintering technology. The fullerene C60 distributed uniformly in the form of clusters, and the average cluster size was less than 1 μm. With increasing C60 content, the electrical conductivity of C60/Cu2SnSe3 composites decreased, while the Seebeck coefficient was enhanced. The thermal conductivity of composites decreased significantly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Shi et al calculated the μH of Cu2SnSe3 materials, and the results showed that the μH was about 52 cm 2 V −1 s −1 at room temperature. The similar Hall mobility is possibly related to the similar density of states effective mass [25,26]. Figure 5 demonstrates the Seebeck coefficients for Cu3Sb1−xGaxSe4 (0 ≤ x ≤ 0.015) compounds.…”
Section: Electrical Performancementioning
confidence: 84%
“…Shi et al calculated the μH of Cu2SnSe3 materials, and the results showed that the μH was about 52 cm 2 V −1 s −1 at room temperature. The similar Hall mobility is possibly related to the similar density of states effective mass [25,26]. Figure 5 demonstrates the Seebeck coefficients for Cu3Sb1−xGaxSe4 (0 ≤ x ≤ 0.015) compounds.…”
Section: Electrical Performancementioning
confidence: 84%
“…Other materials such as manganese silicide based NCs [100] and magnesium silicide based NCs [101,102,103], polycrystalline SnSe embedded with PbTe nanoinclusions [104], Skutterudites CoSb 3 compounds [105] and Yb x Co 4 Sb 12 alloy [106] based NCs, n -type half-Heuslers alloy Hf 0.75 Zr 0.25 NiSn 0.99 Sb 0.01 based NCs [107], p -type half-Heuslers alloy Zr 0.5 Hf 0.5 CoSb 0.8 Sn 0.2 based NCs [108] and Zr 0.25 Hf 0.25 NiSn based NCs [109], BiCuSeO-based NCs [110] and InGaAs alloy embedded with ErAs nanoparticles [111,112] are also studied. Furthermore, some non-TE materials like carbon nanotube [113], C 60 [114,115], graphene [116,117], SiC [118] and platinum nanocrystals [119] are used as nanoconstituents to embed into Bi 2 Te 3 and Sb 2 Te 3 based materials to enhance ZT .…”
Section: Nanocomposites For Thermoelectricitymentioning
confidence: 99%
“…91 A nano Bi and Te molecule slurry are utilized in a screen-printing strategy to create n-and p-type TE intersection with Ag doping. 92 An upgraded TE execution of Cu 2 SnSe 3 -based composites joined with nanofullerene is presented in Zhao et al 93 The high-temperature TE properties of high virtue Bi-doped Mg2(Si, Sn) are introduced in Farahi et al 94 Plasmawave, TE and bolometric nanofinders with a switchable and controllable working instrument are introduced in Viti et al 95 The warm conductivity of GNRs is diminished by presenting pores in them to improve their TE execution, as introduced in Hossain et al 96 The TE transport properties of p-type Bi 2 Te 3 nanofilms with different quintuple layers (QL) were explored in Zhou and Wang. 98 These properties were dependent on monitoring the abdominal muscle for electronic structure estimations and Boltzmann transport conditions.…”
Section: Creating An Electric Potential Via Te Materialsmentioning
confidence: 99%